2017
DOI: 10.1371/journal.pone.0180061
|View full text |Cite
|
Sign up to set email alerts
|

Complex I inhibition augments dichloroacetate cytotoxicity through enhancing oxidative stress in VM-M3 glioblastoma cells

Abstract: The robust glycolytic metabolism of glioblastoma multiforme (GBM) has proven them susceptible to increases in oxidative metabolism induced by the pyruvate mimetic dichloroacetate (DCA). Recent reports demonstrate that the anti-diabetic drug metformin enhances the damaging oxidative stress associated with DCA treatment in cancer cells. We sought to elucidate the role of metformin’s reported activity as a mitochondrial complex I inhibitor in the enhancement of DCA cytotoxicity in VM-M3 GBM cells. Metformin poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 71 publications
2
23
0
Order By: Relevance
“…A mechanism by which DCA may affect cell viability is through inhibition of PDK and increased ROS production. In this regard, DCA was previously shown to inhibit PDK in different tumor cell lines, resulting in dephosphorylation and reactivation of the PDH complex 33 , that promotes oxidative phosphorylation leading to increased ROS production 35 37 . To evaluate whether DCA treatment induced dephosphorylation of PDH in PGL cells, we analyzed by western blotting the phosphorylation status of the PDH-E1α subunit.…”
Section: Resultsmentioning
confidence: 99%
“…A mechanism by which DCA may affect cell viability is through inhibition of PDK and increased ROS production. In this regard, DCA was previously shown to inhibit PDK in different tumor cell lines, resulting in dephosphorylation and reactivation of the PDH complex 33 , that promotes oxidative phosphorylation leading to increased ROS production 35 37 . To evaluate whether DCA treatment induced dephosphorylation of PDH in PGL cells, we analyzed by western blotting the phosphorylation status of the PDH-E1α subunit.…”
Section: Resultsmentioning
confidence: 99%
“…As Ward et al proposed, the detected synergism between DCA and metformin can be best exploited with another pro-oxidant compound (12). As our study suggests, this compound could be PX-478, which would lead to an interesting triple combination.…”
Section: And 5)mentioning
confidence: 51%
“…DCA was found to normalize this axis and thereby induce the apoptosis of cancer cells (8,9). In addition to its effects on the mitochondrial membrane potential, DCA is believed to lead to a signi cant increase in reactive oxygen species (ROS) generation, which plays an important role in the induction of apoptosis (10)(11)(12)(13)(14). By contrast, other authors reported that DCA may function as a sensitizer for ROS induced alterations, but did not signi cantly increase ROS production per se (13,15).…”
Section: Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it impaired DNA and other components of the mitochondrial via the increasing of ROS level (Higgins & Greenamyre, ). Thus, it stimulated apoptosis in different cells, for instance, glioblastoma (Ward, Poff, Koutnik, & D'Agostino, ), leukemia (Diaz‐Aguirre, Velez‐Pardo, & Jimenez‐Del‐Rio, ), cervical (Agarwal, Maurya, Pawar, & Ghosh, ), lung (Hu et al, ), neuroblastoma (Kabiraj et al, ), and liver (Badaboina et al, ) cancerous cells. Other flavonoid, medcarpin, which isolated from medicago sativa, induced apoptosis and defeated multidrug resistance in breast (Le Bail, Champavier, Chulia, & Habrioux, ) and leukemia P388 cells (Gatouillat et al, ).…”
Section: Intracellular Anti‐apoptotic Proteins As Targeted Therapymentioning
confidence: 99%